2007
DOI: 10.1016/j.cveq.2006.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress

Abstract: Oxidative stress refers to the cellular injury and pathologic change that occurs when there is an imbalance favoring oxidants over antioxidants within a living organism. In human medicine, oxidative stress has been implicated in numerous disease processes, which has led to further research into the clinical benefits and efficacy of antioxidant therapy. The evaluation of oxidative stress in the horse has been limited primarily to ischemia-reperfusion injury of the gastrointestinal tract, recurrent airway obstru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 66 publications
1
37
0
2
Order By: Relevance
“…Oxidative stress has also been shown to contribute to acute intestinal mucosal injury following TBI not only through direct injurious effects including lipid peroxidation, disruption of membrane integrity, and apoptosis, but also by involvement in the molecular mechanisms that control intestinal inflammation [5,6,28,29]. One potential defense against the toxicity of oxidative stress is the up-regulation of antioxidant response and antioxidant response element (ARE)-mediated gene products.…”
Section: Discussionmentioning
confidence: 98%
“…Oxidative stress has also been shown to contribute to acute intestinal mucosal injury following TBI not only through direct injurious effects including lipid peroxidation, disruption of membrane integrity, and apoptosis, but also by involvement in the molecular mechanisms that control intestinal inflammation [5,6,28,29]. One potential defense against the toxicity of oxidative stress is the up-regulation of antioxidant response and antioxidant response element (ARE)-mediated gene products.…”
Section: Discussionmentioning
confidence: 98%
“…Racehorses are often transported 698 long distances and endure maximal exercise during training and races and have been shown to suffer 699 frequently from oxidative stress (Hargreves et al, 2002). It has been found that in horses oxidative 700 stress has an effect on the development of airway disease, such as chronic obstructive pulmonary 701 disease and exercise induced pulmonary hemorrhage (EIPH) (Soffler, 2007;Kirschvink et al, 2008). 702…”
Section: Respiratory Illness Post Transport 589mentioning
confidence: 99%
“…In horse, oxidative stress may be a consequence either of several pathological conditions due to biotic and abiotic factors or of physical exercise [9]. The latter is a potent stimulator of ROS production and it has been indicated as causative agent of oxidative stress in horses [10], even if Kirschvink et al [11], comparing the blood oxidant status of healthy and heaves-affected horses after physical exercise, showed that the oxidant status is more affected by the air-way disease than by the exercise.…”
Section: Introductionmentioning
confidence: 99%